Building a robust sulfur host for aqueous Cu-S battery by introducing nitrogen into carbon nanotubes. (December 2022) - Xiao, Chen; Miao, Zhonghao; Yang, Zhengwei; Yu, Haoxiang; Yan, Lei; Zhang, Liyuan; Shu, Jie
Abstract: Aqueous metal-sulfur systems have become a research hotspot in recent years owing to their shuttle-free, great safety, and low cost. Among aqueous metal-sulfur systems, Cu-S battery is a big star for its huge theoretical capacity (3350 mAh g −1 ) based on a four-electron transfer reaction. Nevertheless, it faces the problem of poor cycle stability due to the poor conductivity of sulfur and its large volume expansion. In this study, we use nitrogen-doped multi-walled carbon nanotubes (N-MWCNTs) as an efficient host for loading sulfur, in which the introduction of nitrogen-containing groups into carbon not only increases the electronic conductivity of N-MWCNTs@S but also improves the adsorption behavior between N-MWCNTs and S/CuS/Cu2 S. As a result, N-MWCNTs@S displays high reversible capacity, superior rate performance, and long-span cycling stability. When cycled at 1 A g −1, it can deliver a reversible capacity of 1580.1 mAh g −1 with 95.9% capacity retention after 454 cycles. Graphical abstract: Image, graphical abstract